ANALYSIS PERFORMANCE OF BANK PERKREDITAN RAKYAT AND ENTRY STRATEGY INTO CAPITAL MARKETS - Dewi, Riska; Jimar, Any; Darmawan, Fajar (Institut Agama Islam Negeri Parepare, 2024)
This research examines the influence of financial performance in the form of Return on Assets (ROA), Return on Equity (ROE), Loan to Deposit Ratio (LDR) and Non-Performing Loans (NPL) on the Capital Adequacy Ratio (CAR) at People's Economic Banks registered with the OJK Indonesia for the period January 2018 to December 2022. The data analysis method used is the Error Correction Model (ECM) which analyzes the relationship between the independent variable and the dependent variable in the long term and short term. The results of the analysis show that in the long term the ROA variable has a negative and significant effect on CAR, the ROE variable has a positive and significant effect on CAR, the LDR variable has no significant effect on CAR and the NPL variable has a negative and significant effect on CAR. The results of this research are related to whether BPR will carry out an Initial Public Offering (IPO) from the UUP2SK perspective in looking at opportunities for BPR to enter the capital market.